2020
DOI: 10.1159/000510509
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsies to Evaluate Immunogenicity of Gynecological/Breast Tumors: On the Way to Blood-Based Biomarkers for Immunotherapies

Abstract: <b><i>Background:</i></b> Despite the assumption of breast cancer (BC) as a cold, non-immunogenic tumor, immune checkpoint inhibitor (ICI) therapy is favorable for a subgroup of patients. Immunohistochemical assessment of the programmed cell death ligand 1 (PD-L1) is the only approved companion diagnostic for anti-PD-L1 therapy in metastatic triple-negative BC; however, challenges regarding the standardization of PD-L1 scoring in tumor tissue still remain. Consequently, to select patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 134 publications
0
10
0
Order By: Relevance
“…Breast cancer immunotherapy based on immune checkpoint inhibitors is currently effective for some TNBCs. These patients with TNBC usually show a high TMB and specific characteristics of immune cell infiltration (21,22). In this study, to further explore the immunogenicity of TNBC, i) we investigated differences in immune cell infiltration between high and low tumor mutation loads, differences in key pathways, and correlation to the prognosis of TNBC; ii) we analyzed the difference in immune cell infiltration between the wild and mutation group; iii) In order to identify biomarkers related to the prognosis of TNBC, we screened and identified a prognostic gene related to TNBC, the key mutation gene FAT3.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer immunotherapy based on immune checkpoint inhibitors is currently effective for some TNBCs. These patients with TNBC usually show a high TMB and specific characteristics of immune cell infiltration (21,22). In this study, to further explore the immunogenicity of TNBC, i) we investigated differences in immune cell infiltration between high and low tumor mutation loads, differences in key pathways, and correlation to the prognosis of TNBC; ii) we analyzed the difference in immune cell infiltration between the wild and mutation group; iii) In order to identify biomarkers related to the prognosis of TNBC, we screened and identified a prognostic gene related to TNBC, the key mutation gene FAT3.…”
Section: Discussionmentioning
confidence: 99%
“…With these advances in research, TMB and infiltrating immune cells have emerged as potential prognostic biomarkers for tumour treatment selection. Previous studies have shown that ICIs are effective in some triple-negative breast cancer patients, who typically present with high TMB and specific immune cell infiltration ( 27 - 29 ). It is therefore essential to explore the role played by TMB in all types of breast cancer and its relation to clinical prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis showed that a higher m6A score was positively associated with mutations in TMB and had a poorer prognosis. Immunotherapy based on immune checkpoint inhibitors has some efficacy in TNBC, and these patients often show higher TMB and immune cell infiltration (28)(29)(30). In addition, we observed a strong correlation between the m6A score and PD-L1, a predictor of the immune response, suggesting that the m6A gene may influence the efficacy of immunotherapy and that this score could be used in clinical practice to assist in the formulation of treatment plans.…”
Section: Discussionmentioning
confidence: 99%